Campylobacter jejuni Strain Dynamics in a Raccoon (Procyon lotor) Population in Southern Ontario, Canada: High Prevalence and Rapid Subtype Turnover - Mutschall, Steven K.; Hetman, Benjamin M.; Bondo, Kristin J.; Gannon, Victor P. J.; Jardine, Claire M.; Taboada, Eduardo N. (Frontiers in Veterinary Science, 2020)
Free-ranging wildlife are increasingly recognized as potential reservoirs of disease-causing Campylobacter species such as C. jejuni and C. coli. Raccoons (Procyon lotor), which live at the interface of rural, urban, and more natural environments, are ideal subjects for exploring the potential role that wildlife play in the epidemiology of campylobacteriosis. We studied the prevalence and genetic diversity of Campylobacter from live-captured raccoons on five swine farms and five conservation areas in southwest Ontario. From 2011 – 2013, we collected fecal swabs (n=1096) from raccoons, and (n=50) manure pit samples from the swine farm environment. We subtyped the resulting Campylobacter isolates (n=581) using Comparative Genomic Fingerprinting (CGF) and 114 distinct subtypes were observed, including 96 and 18 subtypes among raccoon and manure pit isolates, respectively. Campylobacter prevalence in raccoons was 46.3%, with 98.7% of isolates recovered identified as C. jejuni. Novel raccoon-specific CGF subtypes (n=40/96) accounted for 24.6% (n=143/581) of Campylobacter isolates collected in this study. Our results also show that C. jejuni is readily acquired and lost in this wild raccoon population and that a high Campylobacter prevalence is observed despite transient carriage typically lasting 30 days or fewer. Moreover, although raccoons appeared to be colonized by species-adapted subtypes, they also harboured agriculture-associated genotypes that accounted for the majority of isolates observed (66.4%) and that are strongly associated with human infections. This suggests that raccoons may act as vectors in the transmission of clinically-relevant C. jejuni subtypes at the interface of rural, urban, and more natural environments.